A model for cooperation networks: promoting information share - Mendonça, Vítor (2012)
Cooperation networks are a promising model for companies. There are currently several models for the creation of this kind of networks. This paper presents a conceptual model for the development of cooperation networks, which aims at promoting the information sharing about business opportunities between members of a specific network. The proposed model is based on a Web Information System, and it is useful in the context of building and managing inter-organizational and/or intra-organizational networks.